Activating transcription factor 6 plays protective and pathological roles in steatosis due to endoplasmic reticulum stress in zebrafish - Cinaroglu, Ayca; Gao, Chuan; Imrie, Dru; Sadler, Kirsten C. (Hepatology (Baltimore, Md.), 2011)
Many etiologies of fatty liver disease (FLD) are associated with the hyperactivation of one of the three pathways composing the unfolded protein response (UPR), which is a harbinger of endoplasmic reticulum (ER) stress. The UPR is mediated by pathways initiated by PRKR‐like endoplasmic reticulum kinase, inositol‐requiring 1A/X box binding protein 1, and activating transcription factor 6 (ATF6), and each of these pathways has been implicated to have a protective or pathological role in FLD. We used zebrafish with FLD and hepatic ER stress to explore the relationship between Atf6 and steatosis. A mutation of the foie gras (foigr) gene caused FLD and hepatic ER stress. The prolonged treatment of wild‐type larvae with tunicamycin (TN), which caused chronic ER stress, phenocopied foigr. In contrast, acute exposure to a high dose of TN robustly activated the UPR but was less effective at inducing steatosis. The sterol regulatory element binding protein transcription factors were not required for steatosis in any of these models. Instead, depleting larvae of active Atf6 either through a membrane‐bound transcription factor peptidase site 1 mutation or an atf6 morpholino injection protected them against steatosis caused by chronic ER stress, but exacerbated steatosis caused by acute TN treatment. Conclusion: ER stress causes FLD. A loss of Atf6 prevents steatosis caused by chronic ER stress but can also potentiate steatosis caused by acute ER stress. This demonstrates that Atf6 can play both protective and pathological roles in FLD. (HEPATOLOGY 2011;)